1992
DOI: 10.1111/j.1365-2109.1992.tb00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and distribution of pond- and hatchery-reared 0+ brown trout, Salmo trutta L., released in a Swedish stream

Abstract: During 1985-88, a tola! of 17500 under-yearling (0+) brown trout. 5a/mo/ru/W L., were released in Laktabacken Creek in Swedish Lapland. Of these, 15500 had been reared in a pond adjacent to the creek during their first summer, where they fed on natural prey. The other 2000 were conventionally reared hatchery fish fed dry food pellets. All fish were released in the autumn (size 6O-70mm) at the confluence of the pond outlet and the creek. Electrofishing revealed that the stocked fish gradually spread downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 33 publications
4
23
1
Order By: Relevance
“…In the present study, the differences in initial weight among wild and reared fish can be explained by lack of natural prey in hatchery fish and/or higher rearing density in artificially reared fish. The influence of rearing method (pond vs. hatchery) on recapture rates of artificially reared fish in this experiment is consistent with some published results (Huet, 1986;Näslund, 1992;Carlstein, 1997). In contrast, Johnsen and Hesthagen (1990) reported that the rearing method is not critical to the recapture rate of stocked brown trout.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, the differences in initial weight among wild and reared fish can be explained by lack of natural prey in hatchery fish and/or higher rearing density in artificially reared fish. The influence of rearing method (pond vs. hatchery) on recapture rates of artificially reared fish in this experiment is consistent with some published results (Huet, 1986;Näslund, 1992;Carlstein, 1997). In contrast, Johnsen and Hesthagen (1990) reported that the rearing method is not critical to the recapture rate of stocked brown trout.…”
Section: Discussionsupporting
confidence: 81%
“…Carlstein (1997) found that T. thymallus reared in a natural pond showed higher post-stocking survival in a lake than fish reared in a conventional hatchery. Näslund (1992) observed higher post-stocking survival in pond-reared brown trout compared to hatchery-reared. Johnsen and Ugedal (1986), however, found no longterm differences in post-stocking feeding of hatchery-reared and wild brown trout.…”
Section: Introductionmentioning
confidence: 82%
“…Given the movement exhibited by the captured trout it is possible that most of the individuals travelled long distances in a downstream direction just one month after their release. The post-stocking movement of salmonids has already been reported in several studies (CRESSWELL, 1981;MORING, 1993;JONSSON et al, 1999), although contradictory results have also been obtained (HEGGENES, 1988;NASLUND, 1998). Additionally, the high vulnerability of stocked fish to predation (JACOBSEN, 2005), which is present in both streams, namely by otters (Lutra lutra), coupled with the possible decline of fish condition during their adaptation to habitat and available food resources may have been responsible for the decrease of stocked trout.…”
Section: Discussionmentioning
confidence: 92%
“…The supplemental stocking included in our study seemed to resurrect the densities of brown trout age-classes older than the stocked fish in the streams undergoing management (see also Jutila, Karttunen & Niemitalo, 1994), although this trend was not consistently observed in post-management streams. Further, Jutila et al (1994) and Näslund (1998) showed that the survival of stocked 1+ and 2+ aged brown trout was relatively high the first summer after the stocking, but decreased during winter. Jokikokko (1990) reported that brown trout disappeared almost completely within 2 years after fry stocking was terminated, because of the lack of natural reproduction in the rapids of the restored timber floating streams in eastern Finland.…”
Section: Re-building Brown Trout Populations 1971mentioning
confidence: 99%